PENDIDIKAN MULTIKULTURAL DALAM MENJAGA KERUKUNAN UMAT BERAGAMA: Studi Tantangan Dinamika Pendidikan Masyarakat Indonesia - Murtadha, Murtadha; Fauzan, Fauzan (Al-Madaris Jurnal Pendidikan dan Studi Keislaman, 2023)
Education is one of the most important parts of human life. With this education, humans have provisions aimed at helping their lives and helping their country. This education can be formal education and non-formal education. Formal education is obtained during learning at school, while non-formal education is obtained from everyday life, including family and society, such as manners and attitudes in daily life in society. In its position, education does not develop alone but is also influenced by the development of other sciences. Until now, education still utilizes philosophy, apart from that it also utilizes the findings of psychology, sociology, anthropology, economics, law, physiology, and so on. As a basis, multicultural education is providing equal learning opportunities to students regardless of their differences (Banks in Wahid, 2016: 288). This means that multicultural education is an educational approach that does not distinguish between cultures, ethnicities, religions and other differences in the sense that all are considered equal, have the same chances and opportunities, and can be harmonious without only favoring each group, let alone ridiculing or considering other groups as inferior. even an enemy to his group. Etymologically, multicultural education is formed by two constituent words, namely the word "education" which means the process of developing a person's attitudes and behavior and "multicultural" diverse cultures or traditions. Thus, multicultural education is education regarding or using an approach to different cultures and traditions. diverse.